Vitamin D and Stroke: Effects on Incidence, Severity, and Outcome and the Potential Benefits of Supplementation - Yarlagadda, Keerthi; Ma, Nicholas; Doré, Sylvain (Frontiers in Neurology, 2020)
Vitamin D serum level has been positively associated with improved cardiovascular health, especially with the reduction of stroke risk. This systemic review summarizes and synthesizes findings from studies relevant to the relationship between vitamin D and stroke risk, severity, and outcome; potential mechanisms explaining such a relationship; and outcomes from vitamin D supplementation. The literature shows that vitamin D deficiency is a significant risk factor for ischemic stroke, with sun exposure, sex, age, race, diabetes, and genetics playing a role as well. Stroke severity and short- and long-term outcomes also worsen with vitamin D deficiency. The neuroprotective mechanisms by which vitamin D operates to mitigate stroke onset and outcomes have yet to be fully studied, but researchers have proposed several pathways, including the promotion of certain neuroprotective growth factors, reduction of arterial pressure through vasodilation, and inhibition of reactive oxygen species. There is some evidence that vitamin D supplementation could lower stroke risk and improve recovery, though outcomes can also be negligible or negative. Although results are mixed and the limitations of vitamin D supplementation merit some caution, vitamin D overall plays a significant role in stroke health. Future research should further develop an understanding of the neuroprotective mechanisms of vitamin D and study how supplementation could be administered effectively in stroke treatment.